Pelayanan Pendidikan dalam Menangani Implikasi Bullying Melalui Sosialisasi Kepada SDN Penikenek, Kecamatan Nagawutung, Kabupaten Lembata - Imelda Jawa Lembu; Kresensia Santrika; Arnoldus Suban Hayon; Johan Semuel Bonat Tamonob; Frans Nyong; Innosensia I.E. Ndiki Satu (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
Education plays an important role in shaping a child's character and personality. Schools as formal educational institutions are not only tasked with imparting knowledge, but are also a place for the formation of social values, morals and behavior. (Cahyani et al., 2021) However, the reality shows that schools are often places where negative behavior emerges, one of which is bullying. The method used in this community service activity uses a participatory method by involving the school in the continuity of socialization activities. The approach taken is to direct and explain efforts to deal with the implications of bullying through the elementary school environment. The place of service was carried out at SDN Penikenek, Nagawutung District, Lembata Regency involving research subjects consisting of the Principal, teachers, students, grades 1-6. Community service activities with the title "educational services in overcoming the implications of bullying at SDN Penikenek in Penikenek Village, Nagawutung District, Lembata Regency". Penikenek Elementary School is an elementary school with 39 students and 11 teachers. This service activity takes place by providing material through outreach and donating wall magazines in the form of magazines related to bullying prevention. Implementation of the outreach program at SDN Penikenek is a strategic step designed to increase students' awareness and understanding regarding the dangers of bullying. In this activity, material about the definition, impact and ways to prevent bullying is delivered using a participatory method involving all elements of the school. This method has proven effective in creating open dialogue, building empathy, and increasing collective commitment to overcoming bullying.